Numerical Modeling of a Marine Propeller Undergoing Surge and Heave Motion - Spyros A. Kinnas; Ye Tian; Abhinav Sharma (International Journal of Rotating Machinery)
A boundary element method (BEM) and a vortex-lattice method (VLM) are extended in order to predict the unsteady performance of propellers subject to rigid body motions. The methods are applied in the case of prescribed surge and heave motions, and the results are compared with those from other methods.